Comprehensive preventive dentistry - Limeback, Hardy (Ames, Iowa : Wiley-Blackwell, 2012)
Comprehensive Preventive Dentistry provides one user-friendly resource that brings together information on the scientific basis and clinical practice of all aspects of preventive dentistry. This thorough and all-encompassing resource offers techniques and strategies for maintaining excellent oral health in patients through a regimen of preventive measures. Comprehensive Preventive Dentistry is grounded in a patient-centered, pre-emptive, and minimally invasive philosophy. The book begins by covering individual diseases, such as caries, periodontitis, and oral cancer, as well as therapies (sea.
11. Ozoneinthepreventionofdentaldiseases -- 12. Protectionofthedentition -- 13. Tootherosion -- 14. Theetiology, diagnosis, andmanagementofdentinhypersensitivity -- 15. Cariesriskassessment -- 16. Fluoridetherapy -- 17. Dentalsealants -- 18. Strategiesforremineralization -- 19. Oralhealthpromotionininfantsandpreschoolagechildren -- 20. High-riskpatients:thefrailolderadultlivinginlong-termcarehomes -- 21. Theeffectivepreventivedentalteam -- 22. Theindependentdentalhygienist.
Includes bibliographical references and index.
Print version record.
Keywords: Preventive dentistry; Teeth -- Diseases -- Prevention; Tooth Diseases -- prevention & control; Comprehensive Dental Care -- methods; Preventive Dentistry -- methods; Tooth Diseases -- diagnosis; Preventive dentistry; Teeth -- Diseases -- Prevention; Electronic books